Feedback Stabilization for a Scalar Conservation Law with PID Boundary Control - Coron, Jean Michel; Tamasoiu, Simona Oana (Chinese annals of mathematics. Serie B, 2015)
This paper deals with a scalar conservation law in 1-D space dimension, and in particular, the focus is on the stability analysis for such an equation. The problem of feedback stabilization under proportional-integral-derivative （PID for short） boundary control is addressed. In the proportional-integral （PI for short） controller case, by spectral analysis, the authors provide a complete characterization of the set of stabilizing feedback parameters, and determine the corresponding time delay stability interval. Moreover, the stability of the equilibrium is discussed by Lyapunov function techniques, and by this approach the exponential stability when a damping term is added to the classical PI controller scheme is proved. Also, based on Pontryagin results on stability for quasipolynomials, it is shown that the closed-loop system subject to PID control is always unstable.